2020
DOI: 10.12740/pp/112967
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for depression. New evidence on selenium deficiency and depressive disorders

Abstract: Cel pracyCelem artykułu jest weryfikacja hipotezy o związku niedoborów selenu z zaburzeniami depresyjnymi przy kontroli zmiennych ubocznych i zakłócających. Na podstawie danych empirycznych porównane zostanie znaczenie niedoborów selenu z innymi czynnikami ryzyka, przy czym nie tylko tymi związanymi z żywieniem.MetodaModel równań strukturalnych oszacowano przy zastosowaniu estymatora diagonalnie ważonych najmniejszych kwadratów ze skorygowaną statystyką testową chi-kwadrat (WLSMV). Obliczono wielkość dziennego… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 30 publications
0
6
1
Order By: Relevance
“…Considering that, among the evaluated farmers, no individual exceeded the intake above the UL established for selenium (400 μg/day), the evaluation of the effects of excessive consumption of this nutrient cannot be performed in this study. The average selenium intake among the evaluated farmers was 81.27 μg/day, higher than that found in other countries such as New Zealand ( 50 ) and Poland ( 51 ). Only 8.8% ( n = 65) of farmers had lower consumption than the Recommended Dietary Allowances (RDAs) of 55 μg/day established for this nutrient.…”
Section: Discussioncontrasting
confidence: 65%
“…Considering that, among the evaluated farmers, no individual exceeded the intake above the UL established for selenium (400 μg/day), the evaluation of the effects of excessive consumption of this nutrient cannot be performed in this study. The average selenium intake among the evaluated farmers was 81.27 μg/day, higher than that found in other countries such as New Zealand ( 50 ) and Poland ( 51 ). Only 8.8% ( n = 65) of farmers had lower consumption than the Recommended Dietary Allowances (RDAs) of 55 μg/day established for this nutrient.…”
Section: Discussioncontrasting
confidence: 65%
“…Studies also focused on the social determinants of (mental) health; these are the conditions in which people are born, live, learn, work, play, and age, and have a significant influence on wellbeing [ 291 ]. Factors such as age, social or socioeconomic status, social support, financial strain and deprivation, food insecurity, education, employment status, living arrangements, marital status, race, childhood conflict and bullying, violent crime exposure, abuse, discrimination, (self)-stigma, ethnicity and migrant status, working conditions, adverse or significant life events, illiteracy or health literacy, environmental events, job strain, and the built environment have been linked to depression, among others [ 52 , 133 , 235 , 236 , 239 , 252 , 269 , 280 , 292 , 293 , 294 , 295 , 296 , 297 , 298 , 299 , 300 , 301 , 302 , 303 , 304 , 305 , 306 , 307 , 308 , 309 , 310 , 311 , 312 , 313 , 314 , 315 , 316 , 317 , 318 , 319 , 320 , 321 , 322 , 323 , 324 , 325 , 326 ,…”
Section: Resultsmentioning
confidence: 99%
“…Various studies on socioeconomic status-related factors have been undertaken [ 239 , 297 ]; the research has shown that a low level of education is linked to depression [ 297 ]. Low income is also related to depressive disorders [ 312 ]. By contrast, high levels of education and income are protective [ 335 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last years some studies have also showed that selenium intake and plasma levels could be inversely associated with depression [ 302 , 303 , 304 , 305 ] and anxiety [ 306 ]. This association was also demonstrated for patients with euthyroid nodular goiter, independently from the thyroid function [ 306 ].…”
Section: Schizophrenia Anxiety and Depressionmentioning
confidence: 99%